Predictive control of muscle responses to arm perturbations in cerebellar patients. Issue 3 (1st September 2000) - Timmann, D; Richter, S; Bestmann, S; Kalveram, K T; Konczak, J
Abstract : OBJECTIVES: To examine changes in predictive control of early antagonist responses to limb perturbations in patients with defined lesions of the cerebellum. METHODS: Eight cerebellar patients and eight sex and age matched control subjects participated. Subjects held a handle that was rotated around the elbow joint. They were instructed to hold the forearm at 90° flexion against a mechanical perturbation. Extensor torque (5 Nm) was applied for 140 ms (pulse), or for 1400 ms (step) through an external motor. Motor responses were tested under two different conditions of anticipatory information. In the expected condition, subjects anticipated and received a pulse. Under the unexpected condition, subjects expected steps, but received unexpected pulses. Biceps and triceps EMG as well as angular kinematics were compared between expected and unexpected pulse perturbations to quantify possible effects of prediction. RESULTS: In all healthy subjects, the degree of overshoot in the return flexion movement was significantly less in expected pulse perturbations compared with unexpected trials. The degree of amplitude reduction was significantly smaller in the patient group than in the control group (22.8% v 40.0%). During the expected trials, latency of peak triceps activity was on average 20% shorter in the control group, but 4% larger in the cerebellar patients. CONCLUSIONS: In the expected condition, controls achieved a significant reduction in angular amplitude by generating triceps activity earlier, whereas the ability to use prediction for adjusting early antagonist responses after limb perturbation was impaired in cerebellar patients.